Promoter identification and transcriptional regulation of the metastasis gene MACC1 in colorectal cancer. Issue 5 (6th June 2013) - Juneja, Manisha; Ilm, Katharina; Schlag, Peter M.; Stein, Ulrike
Abstract : MACC1, Metastasis associated in colon cancer 1, is a newly identified prognostic biomarker for colorectal cancer metastasis and patient survival, when determined in the primary tumor or patient blood. MACC1 induces cell motility and proliferation in cell culture and metastasis in mouse models. MACC1 acts as a transcriptional regulator of the receptor tyrosine kinase gene Met via binding to its promoter. However, no information about the promoter of the MACC1 gene and its transcriptional regulation has been reported so far. Here we report the identification of the MACC1 promoter using a promoter luciferase construct that directs transcription of MACC1. To gain insights into the essential domains within this promoter region, we constructed 5′ truncated deletion constructs. Our results show that the region from −426 to −18 constitutes the core promoter and harbors functional motifs for the binding of AP‐1, Sp1, and C/EBP transcription factors as validated by site directed mutagenesis study. Using electrophoretic mobility shift assay and chromatin immunoprecipitation assay, we demonstrated the physical interaction of these transcription factors to a minimal essential MACC1 core promoter sequence. Knock down of these transcription factors using RNAi strategy reduced MACC1 expression (P < 0.001), and resulted in decrease of cell migration (P < 0.01) which could be specifically rescued by ectopic overexpression of MACC1. In human colorectal tumors, expression levels of c‐Jun and Sp1 correlated significantly to MACC1 (P = 0.0007 and P = 0.02, respectively). Importantly, levels of c‐Jun and Sp1 also showed significant correlation to development of metachronous metastases (P = 0.01 and P = 0.001, respectively). This is the first study identifying the MACC1 promoter and its transcriptional regulation by AP‐1 and Sp1. Knowledge of the transcriptional regulation of the MACC1 gene will implicate in enhanced understanding of its role in cancer progression and metastasis. Highlights: First identification of the gene promoter of the metastasis biomarker MACC1. The core promoter region lies within −18 to −426 bp upstream of TSS. AP‐1, Sp1 and C/EBP bind to the MACC1 promoter and regulate MACC1 expression. Ectopic MACC1 rescues cell migration diminished by knock down of c‐Jun and Sp1. c‐Jun and Sp1 correlate to MACC1 and to metastasis formation in colorectal cancer patients.